The Impact of Color Psychology on Learning Interest and Motivation in E-Learning Visual Communication - Marcellino Imanuel Kurniawan; Alexander Wirapraja (INJECT (Interdisciplinary Journal of Communication), 2026)
This study aims to analyze the influence of color psychology in e-learning visual communication on users’ learning interest and motivation in the JAPANGO application. This research is motivated by the importance of color as a visual element in digital communication that can influence users’ cognitive and emotional responses during the learning process. In the context of e-learning, color functions not only as an aesthetic element but also as a visual stimulus that can enhance users’ attention, engagement, and learning experience. This study employed a quantitative approach with an explanatory design. Data were collected through an online questionnaire using a Likert scale distributed to 224 Indonesian young users who had experience using the JAPANGO mobile-based Japanese language learning application. Data analysis was conducted using Structural Equation Modeling (SEM) with the assistance of AMOS software. The results showed that color psychology had a positive and significant effect on learning interest (β = 0.984; p < 0.001) and learning motivation (β = 1.158; p < 0.001). However, learning interest did not have a significant effect on learning motivation (β = -0.161; p = 0.596). These findings indicate that color-based visual stimuli in e-learning can directly influence users’ learning motivation without necessarily going through gradual cognitive processes. Therefore, color can be utilized as an effective visual communication strategy to enhance users’ digital learning experiences.